New heritage : new media and cultural heritage - Kalay, Yehuda E.; Kvan, Thomas; Afflek, Janice; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 2008)
The use of new media in the service of cultural heritage is a fast growing field, known variously as virtual or digital heritage. New Heritage, under this denomination, broadens the definition of the field to address the complexity of cultural heritage such as the related social, political and economic issues. This book is a collection of 20 key essays, of authors from 11 countries, representing a wide range of professions including architecture, philosophy, history, cultural heritage management, new media, museology and computer science, which examine the application of new media to cultural heritage from a different points of view. Issues surrounding heritage interpretation to the public and the attempts to capture the essence of both tangible (buildings, monuments) and intangible (customs, rituals) cultural heritage are investigated in a series of innovative case studies.
Part 1, New heritage overview: Media, affordances and strategies -- 1 Cultural heritage in the age of new media -- 2 The vanishing virtual: Safeguarding heritage's endangered digital record -- 3 Virtual heritage: Mediating space, time and perspectives -- 4 Through form and content: New media components and cultural heritage sites management, in the Jewish traditional society -- 5 History is 3D: Presenting a framework for meaningful historical representations in digital media -- Part 2, Essence: Digital representation and interpretation of cultural heritage -- 6 Chasing the unicorn?: The quest for "essence" in digital heritage -- 7 Memory capsules: Discursive interpretation of cultural heritage through new media -- 8 Cross-media interaction for the virtual museum: Reconnecting to natural heritage in Boulder, Colorado -- 9 Experiencing the city through a historical digital system -- Part 3, Discourse: The marriage of new media and cultural heritage -- 10 Consuming heritage or the end of tradition: The new challenges of globalization -- 11 The politics of heritage authorship: The case of digital heritage collections -- 12 Explorative shadow realms of uncertain histories -- 13 Making a livable "place": Content design in virtual environment -- Part 4, New heritage in practices: Virtual enviroments -- 14 The components of engagement in virtual heritage environments -- 15 Educational tool or expensive toy? Evaluating VR evaluation and its relevance for virtual heritage -- 16 Designing a virtual museum of architectural heritage -- 17 Place-Hampi: Co-evolutionary narrative and augmented stereographic panoramas, Vijayanagara, India -- 18 Digital songlines: Digitising the arts, culture and heritage landscape of aboriginal Australia
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: kulturní dědictví; digitální média; digitalizace; virtuální realita; inovace; cultural heritage; digital media; digitization; virtual reality; innovations; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online